High-speed process visualization using CuBr-laser; Micro/Nanotechnologies and Electron Devices (EDM) - Trigub M. V. Maksim Viktorovich; Evtushenko G. S. Gennady Sergeevich; Gubarev F. A. Fedor Aleksandrovich; Torgaev S. N. Stanislav Nikolaevich (2012, 2012)
Title screen